1989
DOI: 10.2136/sssaj1989.03615995005300020045x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Affecting Emergence of Winter Wheat Planted with Seed‐Banded Nitrogen Fertilizers

Abstract: Nitrogen use efficiency by cereal crops may be increased by the placement of fertilizer with the seed; however, high N concentrations often cause injury and reduce both germination and emergence. Two studies were conducted under controlled greenhouse conditions to evaluate factors affecting emergence of winter wheat (Triticum aestivum L.) planted with seed‐banded N fertilizers. Soil from the Ap horizon of a Palouse silt loam (fine‐silty, mixed, mesic Pachic Ultic Haploxeroll) was used in both studies. Two N ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
3
8
2
Order By: Relevance
“…Two of the four varieties in this study experienced significant delays and reductions in overall emergence with increasing PCU rate. Mahler, Lutcher, and Everson (1989) also found differences in final emergence among five winter wheat cultivars sown with SCU fertilizers of different release rates in soil with the same m as that used in this study. All cultivars experienced linear declines in emergence with increasing SCU rate; however, the slope of the decline varied among cultivars and ranged from 3.7 to 5.4 kg N per percentage reduction in emergence (Mahler, Lutcher, and Everson 1989) compared to 6 (for Paladin) or 15 (for Bauermeister) kg N per percentage reduction in emergence with PCU in the present study.…”
Section: Variety By N Source-rate Experimentssupporting
confidence: 60%
See 1 more Smart Citation
“…Two of the four varieties in this study experienced significant delays and reductions in overall emergence with increasing PCU rate. Mahler, Lutcher, and Everson (1989) also found differences in final emergence among five winter wheat cultivars sown with SCU fertilizers of different release rates in soil with the same m as that used in this study. All cultivars experienced linear declines in emergence with increasing SCU rate; however, the slope of the decline varied among cultivars and ranged from 3.7 to 5.4 kg N per percentage reduction in emergence (Mahler, Lutcher, and Everson 1989) compared to 6 (for Paladin) or 15 (for Bauermeister) kg N per percentage reduction in emergence with PCU in the present study.…”
Section: Variety By N Source-rate Experimentssupporting
confidence: 60%
“…Seedrow placement of N fertilizer would reduce energy requirements compared to alternative placements (deep band, beside the seed row, or below and beside the seed row) in reducedor no-tillage cereal production systems. However, in-row placement of conventional N fertilizer can inhibit germination and reduce the emergence of cereal crops because of low osmotic potential effects and, in the case of urea-based fertilizers, damage caused by ammonia gas evolution (Severson and Mahler 1988;Bremner and Krogmeier 1989;Mahler, Lutcher, and Everson 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The major benefit of banding urea versus seed placing urea is that banding separates the seed from the fertilizer, thus decreasing seedling injury from ammonia toxicity and allowing for higher rates of N application. Decreased emergence and crop yield occur frequently when urea is seed-placed under dry seedbed conditions and low seedbed utilization (Mahler et al 1989). Lafond et al (2001) speculated that N banded as urea fertilizer in early fall on Black soils may be lost.…”
mentioning
confidence: 99%
“…Some contradictory result was found in low P soil, where P was applied in row placement gave better result than that of mixed with seed and broadcasting (Peterson et al, 1981). In another study it was reported that high doses of P fertilizer mixed with seed have a negative effect on germination (Mahler et al, 1989). This negative effect is higher in light textured soils and in conditions where there is limited moisture.…”
Section: Discussionmentioning
confidence: 99%